Evaluation of Parental Attitudes toward and Awareness of Oral Health in Children during the COVID-19 Pandemic - Shetty, Amarshree A.; Rai, Kavita; Mehrotra, Deepshikha; Hegde, Shipha; Kumara, Kumara; Nayak, U.S. Krishna; D'Souza, Cynthia (Journal of Health and Allied Sciences NU, 2023)
Background Children are one of the most vulnerable groups to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and depend on their parents to supervise and maintain oral hygiene. During this pandemic, disease prevention through education and awareness of the parents is the only way to maintain a child's oral health; therefore, parents must have sufficient knowledge about the ongoing pandemic and its consequences on the oral cavity. This study aims to assess the parental attitudes toward and awareness of oral health of healthy children during the COVID-19 pandemic.Methodology A questionnaire was circulated between May and September 2020 using simple random sampling of the parents of children aged between 6 and 12 years. The questions were close ended and divided into awareness and attitude-based sections so that the parents could choose the appropriate answer.Results and Conclusion In the present study, 50% of the participating parents had the right attitude in challenging times like the pandemic and appropriate knowledge about the same.
Keywords: parental awareness; COVID-19; Oral health; Children